Choosing what to pay attention to - Chad Fulton (Theoretical Economics, 2022)
This paper studies static rational inattention problems with multiple actions and multiple shocks. We solve for the optimal signals chosen by agents and provide tools to interpret information processing. By relaxing restrictive assumptions previously used to gain tractability, we allow agents more latitude to choose what to pay attention to. Our applications examine the pricing problem of a monopolist who sells in multiple markets and the portfolio problem of an investor who can invest in multiple assets. The more general models that our methods allow us to solve yield new results. We show conditions under which the multimarket monopolist would optimally choose a uniform pricing strategy, and we show how optimal information processing by rationally inattentive investors can be interpreted as learning about the Sharpe ratio of a diversified portfolio.
Keywords: D81; D83; G11; 330; Rational inattention; information acquisition; price discrimination; portfolio choice